Factors Affecting Perceived Health Benefits and Use Behaviors in Urban Green Spaces During the COVID-19 Pandemic in Southern China Megacities - Li, Haiwei; Luo, Weijing; Hou, Yongqi; Xia, Yu; Yao, Jing; Kang, Ning; Deng, Congshuang; Sun, Hu; Chen, Chongxian (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic has alienated people from urban green spaces (UGSs) and has various health outcomes for humans. However, little is known about the influential factors of perceived health benefits and use behaviors in UGSs during the COVID-19 pandemic. This study aims to explore the key factors that influence perceived health benefits and use behaviors in UGSs and to assess the mediating role of place attachment in relationships during the COVID-19 pandemic in Chinese megacities. Methods: We conducted an online questionnaire survey from December 2020 to March 2021 in Guangzhou and Shenzhen, China. Six multiple regression models were constructed to investigate the main factors by which UGSs influence citizens’ perceived health benefits and use behaviors. Four mediation models were established using the structural equation modeling (SEM) method to explore the mediating effect of place attachment. Results: A total of 628 questionnaires were included in the analysis. The results revealed that some UGS components (green space access, maintenance, and soundscape) significantly affected perceived health benefits for citizens (physical, mental, and social health) during the COVID-19 pandemic. Conversely, use behaviors (frequency of visits, duration of visits, and activity intensity) were mainly affected by the sociodemographic context but less affected by UGS components. In addition, UGS components were found to significantly predict place attachment, which in turn influenced the perceived health benefits, frequency, and duration of visits. Conclusions: This study distinguished the key factors that affect perceived health benefits and use behaviors during the COVID-19 pandemic: green space access, maintenance, soundscape, and sociodemographic characteristics. Place attachment still needs to be considered when discussing how to encourage citizens to visit UGSs during the pandemic. These findings provide implications for policymakers and landscape planners regarding design and management measures for UGSs that are conducive to coping with pandemics.